(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Evaluate the effect of arrival weight on feedlot growth performance and carcass characteristics of Holstein steers of similar age. Material and Methods: Three hundred calf-fed Holstein steers (age 113 ± 1-day) were distributed in a completely randomly unbalanced design and divided into five categories (105, 112, 117, 123, and 129 kg) of shrunk initial weight (SIW). Calves were weighed on days 1, 112, 224, and 361. Calves were fed steam-flaked corn-based diets. Growth performance and dietary energy were evaluated for each period and the study as a whole (1–361-day). Results: During the rearing period, average daily gain (ADG) increased (linearly effect, p < 0.01) with increasing birth weight. Birthweight was positively associated (p < 0.05) with feedlot arrival weight (R2 = 0.47) and final harvest weight (R2 = 0.36). Overall ADG increased (p < 0.01) with increasing SIW. Dry matter intake increased linearly during the first 224-day but quadratically during the last 137 days. Overall, there was a quadratic effect (p < 0.05) of SIW on gain-to-feed and observed-to-expected dietary NE, with lower efficiencies (4%) for steers in both the lightest and heaviest SIW. Hot carcass weight, Longissimus muscle area, marbling score, and fat thickness increased (linear effect, p ≤ 0.03) as SIW increased, whereas kidney-pelvic-heart fat and yieldgrade were unaffected. Conclusions: The initial arrival weight influences the growth performance, energetic efficiency, and carcass characteristics of Holstein steers of similar age. The effect is more pronounced in the lighter (>112kg) steers. J. Adv. Vet. Anim. Res., 9(1): 59–65, March 2022 http://doi.org/10.5455/javar.2022.i569